Kinetic and Mechanistic Study of N-Chlorosuccinimide Oxidation of 2-Methyl butanol-1 in the Presence of Osmium Tetroxide as Homogeneous Catalyst in Aqueous Alkaline Solution - Kumar, Ashutosh; Singh, Abhishek; K. Singh, Khagesh (Asian Journal of Chemistry, 2010)
The kinetic study of osmium tetroxide catalyzed oxidation of 2-methyl butanol-1 by aqueous alkaline solution of N-chlorosuccinimide shows first-order kinetics with respect to each [Nchlorosuccinimide], [Os(VIII)] and [OH–] and zero order kinetics with respect to [2-methyl butanol-1]. Negligible effect of variation of ionic strength of the medium on the rate of the reaction was observed. Addition of succinimide and mercuric acetate did not affect the rate constant of the reaction. Activation parameter, Ea, DS# and DG# were calculated by the rate contents observed of 30, 35, 40 and 45 ºC. A suitable mechanism in agreement with kinetic observation was proposed.